Konstruksi Andragogi Qur’ani: Analisis Interaksi Edukatif Nabi Musa dan Nabi Khidir dalam Surah Al-Kahfi - Ansorul Alim; David Ricardo; Dwi Ratnasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to construct a comprehensive concept of Quranic Andragogy based on the profound educational interaction between Prophet Musa a.s. and Prophet Khidir a.s. as narrated in Surah Al-Kahfi. Employing systematic library research with a thematic exegesis approach and rigorous content analysis, this research synthesizes Malcolm Knowles’ andragogy theory with core Islamic values and principles. The findings reveal that Quranic Andragogy transcends conventional Western pragmatism by effectively integrating intellectual autonomy with deep spiritual humility (tawadhu). The narrative illustrates three fundamental pillars of this pedagogical model: the urgency of cultivating internal motivation (the need to know), which is driven by a conscious willingness to 'unlearn' ego and preconceptions; the careful management of cognitive conflict within experiential learning processes; and the consistent implementation of a disciplined, ethically guided learning contract. It is concluded that adult education in Islam requires a careful balance between critical reasoning, reflective practice, and spiritual obedience in order to achieve holistic self-transformation that extends beyond the mere transfer of knowledge and information, fostering both intellectual and moral development in learners.